2012
DOI: 10.1371/journal.pone.0035119
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Patterns of Gene Expression in Avian Song Control Brain Regions

Abstract: Photoperiod and hormonal cues drive dramatic seasonal changes in structure and function of the avian song control system. Little is known, however, about the patterns of gene expression associated with seasonal changes. Here we address this issue by altering the hormonal and photoperiodic conditions in seasonally-breeding Gambel's white-crowned sparrows and extracting RNA from the telencephalic song control nuclei HVC and RA across multiple time points that capture different stages of growth and regression. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 82 publications
(127 reference statements)
1
49
0
Order By: Relevance
“…A possible mechanism through which postsynaptic activity can influence neuronal addition is by activity-induced regulation of genes encoding molecules that promote survival of adult-born HVC neurons, axon path finding, and/or synapse formation (33,34). Interestingly, activity-induced guidance molecules are seasonally regulated in RA neurons of WCS; microarray analysis of cDNA extracted from RA revealed that the expression of guidance cue genes, including netrin 4 and galectin, is increased in breeding-condition birds (35). Activity in RA may modulate recruitment via activity-induced trophic factors produced by target neurons that are transported retrogradely to influence the survival of new neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible mechanism through which postsynaptic activity can influence neuronal addition is by activity-induced regulation of genes encoding molecules that promote survival of adult-born HVC neurons, axon path finding, and/or synapse formation (33,34). Interestingly, activity-induced guidance molecules are seasonally regulated in RA neurons of WCS; microarray analysis of cDNA extracted from RA revealed that the expression of guidance cue genes, including netrin 4 and galectin, is increased in breeding-condition birds (35). Activity in RA may modulate recruitment via activity-induced trophic factors produced by target neurons that are transported retrogradely to influence the survival of new neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In canaries, expression levels of brainderived neurotrophic factor (BDNF) mRNA in HVC are higher in singing birds compared with nonsinging birds, and infusion of BDNF protein near HVC in nonsinging birds increases neuronal addition in HVC (16,36). Microarray analysis also revealed that the expression of the proneurogenic genes, including insulin-like growth factor 1 and neuromodulin, is increased in breeding-condition WCS (35). In HVC, the mRNA expression of sex steroid receptors, which facilitate the retrograde transport of trophic factors bound to their receptor toward the neuronal soma, also increases during breeding conditions (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The retrograde transport of activity-induced trophic factors produced by target neurons that influence the survival of new HVC RA neurons may be modulated by activity in RA. Microarray analysis also showed that the expression of proneurogenic genes, including IGF-1 and neuromodulin, is increased in RA of breeding-condition birds (Thompson et al 2012). In HVC, the expression of mRNA for sex steroid receptors, which facilitate the retrograde transport toward the neuronal soma of trophic factors bound to their receptor, also increases during breeding conditions (Fusani et al 2000;Jezierski and Sohrabji 2003;Fraley et al 2010).…”
Section: Neurogenesis In Adult Birdsmentioning
confidence: 94%
“…3) (Warren et al 2010;Thompson et al 2012). Thompson et al (2012) identified 132 genes in HVC cells in adult male white-crowned sparrows (Zonotrichia leucophrys), which changed in expression between breeding and nonbreeding physiological conditions when compared with gene expression in RA, a nonneurogenic nucleus . In general, genes that promote proliferation, angiogenesis, and neurite extension were up-regulated, whereas genes that support programmed cell death were down-regulated in HVC under breeding conditions.…”
Section: Neurogenesis In Adult Birdsmentioning
confidence: 99%
See 1 more Smart Citation